CLINICAL PROFILE AND OUTCOMES OF NEONATES WITH RESPIRATORY DISTRESS MANAGED WITH BUBBLE CONTINUOUS POSITIVE AIRWAY PRESSURE: A TERTIARY CARE HOSPITAL EXPERIENCE (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Respiratory distress is a leading cause of neonatal morbidity and mortality, particularly in preterm infants. Bubble continuous positive airway pressure (bCPAP) has emerged as an effective non-invasive respiratory support modality. This study aimed to evaluate the clinical profile and outcomes of neonates with respiratory distress managed with bCPAP. Methods: A prospective observational study was conducted over 12 months (April 2023-April 2024) at a tertiary care neonatal unit. Neonates with respiratory distress (Downes/Silverman-Anderson score 4-6) were included. Demographic data, clinical parameters, duration of CPAP support, and outcomes were analyzed. Statistical analysis was performed using chi-square and Fisher's exact tests. Results: Of 165 neonates enrolled, 68.5% were preterm. The most common etiology was respiratory distress syndrome (RDS, 61.8%), followed by transient tachypnea of newborn (TTN, 17.0%). Overall success rate of bCPAP was 77.0%. CPAP failure requiring mechanical ventilation occurred in 23.0%, with 17.6% mortality. Gestational age significantly influenced outcomes, with